Preparation method and application of CDs@LDHs molecularly imprinted polymer
By designing CDs@LDHs molecularly imprinted polymers, combining carbon dots and layered dihydroxides, the shortcomings of the existing nitrizole detection methods in terms of specificity, sensitivity and cost are solved, and efficient and accurate nitrizole trace detection is achieved.
Patent Information
- Application Number
- CN202411855063.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2044-12-17
AI Technical Summary
The existing nitrizole detection methods have shortcomings in specificity, sensitivity, measurement result stability, accuracy and cost, especially in the field of nitrizole trace detection, the detection efficiency is poor and the cost is high.
A CDs@LDHs molecular imprinted polymer was designed, and detection materials with high sensitivity and specificity were prepared by combining carbon dots (CDs), layered dihydroxides (LDHs) and molecular imprinted polymers, using nitrizole as template molecules. The method includes reacting LDHs with template molecules and functional monomers, followed by adding CDs, tetraethyl silicate and ammonia water for secondary reaction and elution to prepare CDs@LDHs molecularly blotting polymer.
It realizes accurate measurement of nitrizole concentration, has the advantages of high sensitivity, strong specificity, low detection cost, reusable and good stability, and is suitable for nitrizole trace detection.
Smart Images

Figure CN119306997B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of organic polymer compounds, and specifically relates to a preparation method and application of a CDs@LDHs molecular imprinting polymer. Background Art
[0002] Triazole fungicides are organic nitrogen-containing heterocyclic fungicides containing 1,2,4-triazole rings. Myclobutanil is one of the commonly used fungicides. Its main mechanism is to inhibit the biosynthesis of ergosterol in pathogenic bacteria, thereby effectively preventing and controlling crop diseases caused by fungi such as ascomycetes and basidiomycetes. Myclobutanil has the characteristics of high efficiency, good broad spectrum, long-lasting action, good stress resistance and easy absorption by plant roots and stems. On the one hand, these characteristics make the disease and pest control effect significant. However, if used excessively, the easy absorption and other characteristics will make myclobutanil more likely to remain in plants and water bodies, thereby endangering human health. Therefore, it is very necessary to develop efficient and rapid trace detection technology for myclobutanil in crops. At present, the main detection methods of myclobutanil include gas chromatography-mass spectrometry, infrared spectroscopy, gas chromatography and high performance liquid chromatography, but these methods still have many shortcomings in terms of specificity, detection sensitivity, measurement stability and accuracy for myclobutanil, and there are also problems of poor detection efficiency and high detection cost. Molecular imprinting polymers are often used as sensing materials for pesticide content detection because of their advantages of good selectivity and sensitivity, simple preparation and low cost.
[0003] Molecularly imprinted polymers are polymers prepared based on a principle similar to that of "antigen-antibody". They are synthesized by cross-linking monomers based on imprinted molecules. During this process, multiple sites that are bonded to imprinted molecules (also known as template molecules) are formed. These sites can be retained after the imprinted molecules are eliminated, forming molecularly imprinted polymers that can specifically recognize and adsorb structural analogs of imprinted molecules. Applying molecularly imprinted polymers to the field of chemical sensing can convert specific recognition at the microscopic level into measurable light and electrical signals, which can achieve rapid, accurate and real-time monitoring of target substances.
[0004] Carbon dots, also known as carbon quantum dots, referred to as CDs, are carbon-based nanoparticles with a size of less than 10nm. Carbon dots are a new type of nano-fluorescent material. Because they have the advantages of low toxicity, good biocompatibility, strong and stable fluorescence properties and easy surface modification, they have broad application prospects in the fields of fluorescent probes, biosensors, food testing, etc. Layered double hydroxides, referred to as LDHs, are layered compounds composed of several layers of positively charged metal hydroxide layers and negatively charged anions in the middle of the layers. They have the advantages of exchangeable interlayer anions, adjustable metal hydroxide structure, large specific surface area and low environmental pollution. Therefore, they are ideal materials as nanomaterial carriers in the fields of pollution prevention and control, medical treatment, food, etc.
[0005] Chinese patent CN111635552A discloses a preparation method and application of a myclobutanil molecular imprinted inverse opal photonic crystal hydrogel sensor. The preparation method comprises the following steps: firstly preparing a SiO2 microsphere emulsion, and using the emulsion to prepare a glass sheet with an opal structure photonic crystal; then thermally polymerizing a myclobutanil precursor solution and an initiator azobisisobutyronitrile in the three-dimensional network structure of the opal to form an myclobutanil imprinted structure; finally, washing away the myclobutanil molecules to obtain a molecular imprinted photonic crystal hydrogel film; the myclobutanil imprinted cavity in the molecular imprinted photonic crystal hydrogel film can quickly capture the myclobutanil molecules, causing the Bragg diffraction peak thereof to red-shift, thereby converting the chemical signal into an optical signal, thereby realizing rapid detection of the myclobutanil concentration in the sample.
[0006] When myclobutanil is complexed with the specific recognition sites on the molecularly imprinted photonic crystal hydrogel film, the structure of the photonic crystal in the hydrogel film will change due to the adsorption of myclobutanil molecules, resulting in a red shift in the position of the Bragg diffraction peak generated when light passes through the photonic crystal. This red shift phenomenon is in a strict linear relationship with the concentration of myclobutanil molecules, so the concentration of myclobutanil in the sample can be indirectly measured by measuring the position change of the Bragg diffraction peak. However, the hydrogel material is a material that easily absorbs or loses water, and the volume expansion or contraction of the hydrogel will cause the periodic structure of the photonic crystal to be distorted. This distortion will change the periodic distribution of the refractive index of the photonic crystal, thereby affecting its Bragg diffraction peak position. Therefore, the storage conditions of the hydrogel film in this patent are relatively strict, and long-term storage will affect the measurement accuracy.
[0007] Due to the shortcomings of existing myclobutanil detection technology in the field of trace myclobutanil detection in terms of specificity, sensitivity, stability and accuracy of measurement results, as well as detection efficiency and cost, designing a molecular imprinting polymer suitable for trace myclobutanil detection based on the characteristics of molecular imprinting polymers in chemical sensing to solve the above problems is one of the important research directions for detection personnel. Summary of the invention
[0008] The purpose of the present invention is to provide a method for preparing a CDs@LDHs molecular imprinted polymer to solve the deficiencies in the current myclobutanil measurement methods in terms of specificity, sensitivity, stability of measurement results, accuracy and cost. The present invention also provides an application of the CDs@LDHs molecular imprinted polymer, which can be used to accurately measure the myclobutanil content in crops.
[0009] To achieve the above object, the technical solution adopted by the present invention is:
[0010] The preparation method of the CDs@LDHs molecular imprinted polymer of the present invention is to react LDHs with a template molecule and a functional monomer, then sequentially add CDs, tetraethyl silicate and an ammonia solution for a secondary reaction, and elute to finally obtain the CDs@LDHs molecular imprinted polymer.
[0011] The CDs are prepared by hydrothermal reaction of citric acid, ethanol and silane coupling agent; the silane coupling agent is KH792; the added amount ratio of citric acid, ethanol and silane coupling agent is (0.045-0.055): 1:1, wherein the unit of citric acid is g, and the unit of ethanol and silane coupling agent is mL; the hydrothermal reaction temperature is 175-190°C, and the hydrothermal reaction time is 4.5-7h.
[0012] The LDHs is Mg / Fe-LDHs, which is prepared by coprecipitating magnesium chloride hexahydrate and ferric chloride hexahydrate by introducing a sodium hydroxide solution; the concentration of the sodium hydroxide solution is 9.0-10.5 mol / L; the ratio of the added amounts of magnesium chloride hexahydrate, ferric chloride hexahydrate and the sodium hydroxide solution is (0.65-0.75):(0.15-0.25):1, wherein the units of magnesium chloride hexahydrate and ferric chloride hexahydrate are g, and the unit of the sodium hydroxide solution is mL; the coprecipitation temperature is 20-40°C, and the coprecipitation time is 12-20 min.
[0013] The ratio of the added amounts of LDHs, functional monomer, tetraethyl silicate and ammonia water is 1:14:60:(7-10), wherein the unit of LDHs is mg, and the unit of functional monomer, tetraethyl silicate and ammonia water is µL; the molar ratio of the template molecule to the functional monomer is 1:3; the template molecule is myclobutanil, and the functional monomer is 3-aminopropyltriethoxysilane.
[0014] The primary reaction time is 60-120 minutes; the secondary reaction time is 5-6.5 hours; a mixture of methanol and acetic acid is used for elution, and the mass ratio of methanol to acetic acid is (8-10):1.
[0015] The application of the CDs@LDHs molecular imprinting polymer of the present invention is to prepare the CDs@LDHs molecular imprinting polymer into a test solution, perform fluorescence quenching on the test solution and a buffer solution with different concentrations of myclobutanil standard solutions, measure the corresponding relationship between the fluorescence quenching rate of the test solution and the myclobutanil concentration, and thus obtain a standard curve; the test solution and the buffer solution are re-prepared and the crop is made into a crop grinding solution, the test solution and the buffer solution are used with the crop grinding solution containing myclobutanil for fluorescence quenching, detect the fluorescence quenching rate of the re-prepared test solution, and obtain the myclobutanil concentration in the crop grinding solution according to the corresponding relationship on the standard curve.
[0016] in:
[0017] The preparation method of the crop grinding liquid is as follows: weigh the crop and grind it into powder, add ethanol and shake it well, refrigerate it for 12 hours, take it out, ultrasonicate it for 1 hour, and centrifuge it at a centrifugal speed of 3200-4500 rmin -1 , the centrifugation time is 30-45min, the supernatant is collected, and ethanol is added to the solid obtained by centrifugation, and the above step of collecting the supernatant is repeated twice, and the supernatant obtained three times is mixed to obtain the crop grinding liquid. The ratio of ethanol to crop added each time is (3-50):1, the unit of ethanol is mL, and the unit of crop is g.
[0018] The test solution is prepared by dispersing CDs@LDHs molecular imprinting polymer in ethanol, and the concentration of CDs@LDHs molecular imprinting polymer is 0.25 mg / mL; the buffer solution is a mixture of disodium hydrogen phosphate (Na2HPO4) and sodium dihydrogen phosphate (NaH2PO4), and the pH value of the buffer solution is 8; the volume ratio of the test solution, the buffer solution, the myclobutanil standard solution and the crop grinding solution is 4:1:2:2.
[0019] The fluorescence quenching rate is measured by a fluorescence spectrophotometer; the fluorescence quenching temperature is 20-35° C., and the fluorescence quenching time is 55 min.
[0020] The concentration of the myclobutanil standard solution is 0-0.012µg / mL; the detection range of the myclobutanil concentration in the crop grinding liquid is 0-0.3053µg / g, where g represents 1g of crop mass.
[0021] The concentration values of the myclobutanil standard solution are 0µg / mL, 0.0005µg / mL, 0.0012µg / mL, 0.0018µg / mL, 0.0032µg / mL, 0.0045µg / mL, 0.0059µg / mL, 0.0078µg / mL, 0.0096µg / mL and 0.012µg / mL, respectively.
[0022] The present invention is based on the related properties of carbon dots, layered double hydroxides and molecular imprinting polymers, and prepares CDs@LDHs molecular imprinting polymers by compounding the three and using myclobutanil as a template molecule. During detection, when myclobutanil in crops is compounded with CDs@LDHs molecular imprinting polymers, static fluorescence quenching of carbon dots will occur. By detecting the fluorescence quenching rate of CDs@LDHs molecular imprinting polymers before and after quenching, the myclobutanil concentration can be quantitatively calculated according to the standard curve. Molecular imprinting polymers have the advantages of small dosage, high sensitivity, strong specificity for myclobutanil recognition, etc., and have great development potential in the field of trace detection.
[0023] The beneficial effects of the present invention are as follows:
[0024] (1) Since the fluorescence lifetime of CDs is related to the rate at which the electrons on the excited state energy level of CDs return to the ground state, the faster the rate, the shorter the fluorescence lifetime. The present invention designs molecular imprinting polymers based on the static quenching principle; that is, amino and amide groups are introduced on the surface of carbon dots through coupling agents, so that the carbon dots form a new conjugated structure with weaker fluorescence performance through hydrogen bonding with the cyano group in myclobutanil in the ground state, thereby causing the fluorescence absorption spectrum of the CDs@LDHs molecular imprinting polymer to change. Therefore, the present invention does not affect the decay process of the excited state CDs molecules, that is, it does not affect the rate at which they return to the ground state, so the CDs fluorescence lifetime remains unchanged, and the CDs@LDHs molecular imprinting polymer can be repeatedly recycled, and the detection cost is greatly reduced.
[0025] (2) The present invention adds Mg / Fe-LDHs and adjusts the ratio of n(Mg):n(Fe) to utilize the easy exchangeability of interlayer anions of Mg / Fe-LDHs (e.g. Cl - The maximum exchange capacity and interlayer Cl - The content is basically the same) and the large anion exchange capacity can exchange ions with negatively charged CDs to embed CDs into the positively charged metal hydroxide layer of Mg / Fe-LDHs, reducing the contact between CDs molecules, thereby reducing the probability of partial CDs energy loss through non-radiative transitions. The repulsive force between positive charges further reduces the probability of spontaneous fluorescence quenching due to contact between CDs molecules, thereby improving the stability of multiple detections. CDs@LDHs molecular imprinting polymers can be prepared in advance and stored for a long time, further improving the detection efficiency.
[0026] In addition, by utilizing the better interlayer spacing adjustment flexibility of Mg / Fe-LDHs and adjusting the n(Mg):n(Fe) ratio according to the molecular size and shape of the target molecule (myclobutanil), Mg / Fe-LDHs can have a suitable interlayer spacing and charge density, thereby improving the specificity and recognition performance of the specific molecular (myclobutanil) structure.
[0027] (3) When preparing CDs@LDHs molecular imprinting polymers according to the present invention, the functional monomer 3-aminopropyltriethoxysilane and the template molecule myclobutanil form a prepolymer complex through hydrogen bonding, so that myclobutanil maintains a reasonable orientation and position during the preparation of the molecular imprinting polymer. Subsequently, tetraethyl silicate and ammonia water are added to form a polymer with a three-dimensional network structure through a polymerization reaction. Tetraethyl silicate is a crosslinking agent that promotes the free radical polymerization reaction of 3-aminopropyltriethoxysilane, the template molecule myclobutanil and Mg / Fe-LDHs; ammonia water acts as an inducer or initiator to induce the structural reformation of polysiloxane, and finally obtains a network structure with more stable chemical and mechanical properties. This structural reformation helps to improve the structural stability of the specific recognition site in the CDs@LDHs molecular imprinting polymer after the template molecule is eluted; in addition, it can promote the hydrolysis and polycondensation of tetraethyl silicate and increase the crosslinking reaction rate.
[0028] (4) In addition, through experimental verification, CDs@LDHs molecular imprinting polymer has the advantages of wide linear range and high sensitivity when detecting the content of myclobutanil in crops, especially being able to effectively detect trace levels of myclobutanil; it has specificity for the detection of myclobutanil, and the test results are accurate (the recovery rate range is less than 100% and close to 100%), and the measurement results have good reproducibility (RSD=3.2); CDs@LDHs molecular imprinting polymer also has the advantages of being pre-stored, small in dosage, simple in operation, low in cost, and can be repeatedly recycled. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 is the ultraviolet absorption spectrum of CDs in Example 1;
[0030] Figure 2 is the infrared spectrum of CDs in Example 1;
[0031] Figure 3 is the fluorescence spectrum of CDs in Example 1;
[0032] Figure 4 is the infrared spectrum of Mg / Fe-LDHs in Example 1;
[0033] Figure 5 The UV absorption spectra of the CDs@LDHs molecularly imprinted polymer after the first elution and the fifth elution in Example 1;
[0034] Figure 6 The infrared spectra of the CDs@LDHs molecular imprinting polymer before and after elution in Example 1 and the CDs@LDHs non-molecular imprinting polymer in Comparative Example 1;
[0035] Figure 7 The fluorescence spectra of CDs@LDHs molecular imprinting polymer before and after elution and CDs in Example 1;
[0036] Figure 8 Graph showing the relationship between the fluorescence quenching rate and the reaction time of the CDs@LDHs molecular imprinting polymer in Example 1 and the CDs@LDHs non-molecular imprinting polymer in Comparative Example 1;
[0037] Fig. 9 Graph showing the relationship between the fluorescence quenching rate of the CDs@LDHs molecular imprinting polymer in Example 1 and the CDs@LDHs non-molecular imprinting polymer in Comparative Example 1 and the pH of the buffer solution;
[0038] Fig.10 It is a relationship diagram between the linear relationship between fluorescence quenching rate and myclobutanil concentration and the added amount of CDs@LDHs molecular imprinting polymer in Example 1 and CDs@LDHs non-molecular imprinting polymer in Comparative Example 1;
[0039] Fig.11 The graph is a relationship between the fluorescence quenching rate of the CDs@LDHs molecular imprinted polymer in Example 1 and the CDs@LDHs non-molecular imprinted polymer in Comparative Example 1 and the concentration of myclobutanil;
[0040] Fig.12 This is the standard curve of fluorescence quenching rate-myclobutanil concentration of CDs@LDHs molecular imprinting polymer in Example 1. DETAILED DESCRIPTION
[0041] The present invention is specifically described and illustrated below in conjunction with embodiments.
[0042] Example 1
[0043] Preparation of CDs solution:
[0044] Weigh 0.503g of citric acid, add 10.0mL of anhydrous ethanol and 10.0mL of KH792 silane coupling agent, and after ultrasonic dispersion treatment, transfer the solution to a hydrothermal synthesis reactor and place it in an electric blast drying oven. Set the reactor temperature to 180°C, react for 6h, cool to room temperature after the reaction, and extract to obtain a clear yellow-brown liquid. The components, molecular structure, and fluorescence properties of the yellow-brown liquid were characterized.
[0045] Use UV spectrophotometer to conduct qualitative analysis on yellow-brown liquid; Figure 1 (ordinate: absorbance / A, horizontal axis: excitation wavelength / nm) shows that it has characteristic absorption peaks at 221nm and 355nm, and the maximum absorption peak is located at 221nm, which is a typical ultraviolet spectrum feature of carbon dots. The molecular structure of carbon dots was analyzed using Fourier transform infrared spectrometer; Figure 2 (Vertical axis: percent transmittance / T%, horizontal axis: wave number / cm -1 ) as shown in 3200-3500cm-1 The broad peak is the stretching vibration peak of -OH, 2933.72 cm -1 The stretching vibration peak of -CH appears at 3282.31cm -1 and 1560.41cm -1 The stretching vibration peaks of -NH and -C=ONR appear at 1116.78 cm -1 and 1061.34cm -1 The stretching vibration peaks of Si-O-Si and Si-OC appeared respectively. The surface of the carbon dots contained amino, hydroxyl and amide bonds through infrared spectroscopy. The fluorescence properties of CDs were measured by fluorescence spectrophotometer; Figure 3 As shown (ordinate: fluorescence intensity / F, abscissa: wavelength / nm), the fluorescence spectrum of carbon dots has a peak at 458nm, and the fluorescence performance is good.
[0046] Preparation of Mg / Fe-LDHs powder:
[0047] Weigh 0.710g magnesium chloride hexahydrate and 0.205g ferric chloride hexahydrate, add 25mL deionized water respectively, and disperse by ultrasonic to obtain a solution. Transfer the ferric chloride hexahydrate solution to a three-necked flask, add magnesium chloride hexahydrate solution to the three-necked flask at 25°C and nitrogen atmosphere, stir for 5min, and then continue to add 1.0mL of 10mol / L sodium hydroxide solution, coprecipitate for 15min, and obtain a brown-yellow solution after the reaction is completed; centrifuge the brown-yellow solution at 4000rpm for 20min, wash several times until the pH is maintained at neutral, and then make up to 50mL with ultrapure water, disperse by ultrasonic for 5min, and obtain an orange-yellow Mg / Fe-LDHs suspension. Finally, put the suspension into a freeze dryer and dry for 12h and grind to obtain an orange-yellow Mg / Fe-LDHs powder. The molecular structure of the Mg / Fe-LDHs powder was characterized.
[0048] The molecular structure of Mg / Fe-LDHs was analyzed using Fourier transform infrared spectrometer; Figure 4 (Vertical axis: percent transmittance / T%, horizontal axis: wave number / cm -1 ) shown at 3487.47cm -1 The -OH stretching vibration peak can be observed at 1633.70 cm -1 The absorption peak of water molecule bending vibration between material layers is formed at 1477.47cm -1 and 570.95cm -1 The absorption peaks at are the vibration absorption peaks of Mg-O bond and Fe-O bond respectively.
[0049] Preparation of CDs@LDHs molecularly imprinted polymers:
[0050] Take 25 mg of Mg / Fe-LDHs powder and ultrasonically disperse it with 40 mL of ethanol for 30 min, then add the template molecule myclobutanil and 350 µL of 3-aminopropyltriethoxysilane in sequence, the molar ratio of myclobutanil to 3-aminopropyltriethoxysilane is 1:3, turn on magnetic stirring, stir for 1 h, continue to add 0.1 mL of LCDs solution, magnetically stir for 30 min, then add 1.5 mL of tetraethyl silicate, stir evenly, then drop a mixed solution of 200 µL of ammonia water and 800 µL of ultrapure water, continue the reaction for 6 h, let it stand for 18 h and then centrifuge to obtain the CDs@LDHs molecular imprinting polymer before elution.
[0051] After that, the product was washed, centrifuged and washed again several times with an eluent having a mass ratio of methanol to acetic acid of 9:1, in order to remove the template molecule myclobutanil until the characteristic peak of myclobutanil could not be detected by ultraviolet spectrophotometer. The washed product was centrifuged and dried in a freeze dryer overnight to obtain CDs@LDHs molecular imprinting polymer (i.e., CDs@LDHs molecular imprinting polymer after elution).
[0052] In addition, CDs@LDHs non-molecularly imprinted polymers were prepared according to the method described in Example 1, except that the template molecule myclobutanil was not added.
[0053] The UV spectrum of CDs@LDHs molecular imprinting polymer is shown in Figure 5 As shown (ordinate: absorbance / A, abscissa: excitation wavelength / nm; from top to bottom in the figure are the measurement curves after the first elution and the measurement curves after the fifth elution), the ultraviolet absorption at 252nm of the first elution is the characteristic absorption peak of myclobutanil, and the characteristic absorption peak of myclobutanil disappears after the fifth elution, indicating that the template molecule myclobutanil in the CDs@LDHs molecular imprinting polymer has been completely washed away.
[0054] The molecular structures of CDs@LDHs non-molecularly imprinted polymers and CDs@LDHs molecularly imprinted polymers before and after elution were analyzed using Fourier transform infrared spectroscopy; Figure 6 As shown (ordinate: percent transmittance / T%, horizontal axis: wave number / cm -1 ; From top to bottom in the figure are the measurement curves of CDs@LDHs molecular imprinting polymer before elution, CDs@LDHs non-molecular imprinting polymer and CDs@LDHs molecular imprinting polymer after elution), among which the CDs@LDHs molecular imprinting polymer before elution is at 2330.82cm -1The absorption peak of C≡N appears at 110 cm2. Due to the hydrogen bonding between myclobutanil and CDs@LDHs molecular imprinting polymer, the C≡N in CDs@LDHs molecular imprinting polymer moves to a higher wavelength of 110 cm2 relative to myclobutanil. -1 , while the eluted CDs@LDHs molecular imprinting polymer and CDs@LDHs non-molecular imprinting polymer did not show the absorption peak of C≡N. In addition, the infrared spectrum showed the stretching vibration peak of =CH (located at 3077.46cm -1 、3091.31cm -1 、3079.24cm -1 ), due to the hydrogen bonding force between myclobutanil and the functional monomer 3-aminopropyltriethoxysilane in the polymer, the CDs@LDHs molecularly imprinted polymer shifted to a lower wavelength of 13 cm compared with the CDs@LDHs non-molecularly imprinted polymer. -1 Left-right movement; combination Figure 5 Analysis showed that the template molecule myclobutanil was successfully imprinted into the CDs@LDHs molecularly imprinted polymer. Figure 6 At the same time, the asymmetric stretching vibration peaks of Si-O-Si can be found (located at 1139.27 cm -1 、1139.93cm -1 、1140.82cm -1 ) and Si-OC vibration peaks (located at 1052.72 cm -1 、1055.06cm -1 、1057.36cm -1 ), the results show that the carbon dots are effectively combined with the functional monomer 3-aminopropyltriethoxysilane. In addition, the peaks of Mg-O bonds also appeared in the spectrum (located at 1419.21cm -1 、1416.60cm -1 、1419.73cm -1 ) and the peaks of Fe-O bonds (located at 660.84 cm -1 、661.37cm -1 、660.21cm -1 ), the results showed that CDs@LDHs molecular imprinting polymer was successfully prepared.
[0055] The fluorescence intensity changes of CDs@LDHs molecular imprinting polymers before and after elution were detected by fluorescence spectrophotometer and compared with the fluorescence spectrum of CDs ( Figure 3 ) for comparison, such as Figure 7As shown (ordinate: fluorescence intensity / F, abscissa: wavelength / nm; at 450nm, from top to bottom are the measurement curves of CDs, CDs@LDHs molecular imprinting polymer before and after elution), the fluorescence intensity of CDs@LDHs molecular imprinting polymer decreases after the reaction with myclobutanil, but it can be roughly restored to the fluorescence intensity of CDs after washing, indicating that it is regenerable and can be used multiple times.
[0056] Example 2
[0057] Preparation of CDs solution: 0.45 g of citric acid was added, the kettle temperature was set to 190° C., the reaction time was 4.5 h, and the remaining steps were the same as in Example 1.
[0058] Preparation of Mg / Fe-LDHs powder: 0.65 g of magnesium chloride hexahydrate, 0.15 g of ferric chloride hexahydrate, and 9.0 mol / L of sodium hydroxide solution; at 20° C. and in a nitrogen atmosphere, magnesium chloride hexahydrate solution and sodium hydroxide solution were added in sequence, and the coprecipitation reaction was carried out for 20 minutes. The remaining steps were the same as in Example 1.
[0059] Preparation of CDs@LDHs molecular imprinting polymer: The first blending time was 120 min, and the second blending was divided into two steps. The first step was to add CDs and stir for 30 min. The second step was to add 1.5 mL of tetraethyl silicate, 175 µL of ammonia water and ultrapure water, and stir for 4.5 h. The mass ratio of methanol to acetic acid was 8:1. The remaining steps were the same as in Example 1.
[0060] Example 3
[0061] Preparation of CDs solution: 0.55 g of citric acid was added, the kettle temperature was set to 175° C., the reaction time was 7 h, and the remaining steps were the same as in Example 1.
[0062] Preparation of Mg / Fe-LDHs powder: 0.75 g of magnesium chloride hexahydrate, 0.25 g of ferric chloride hexahydrate, and 10.5 mol / L of sodium hydroxide solution; at 40° C. and in a nitrogen atmosphere, magnesium chloride hexahydrate solution and sodium hydroxide solution were added in sequence, and the coprecipitation reaction was carried out for 12 minutes. The remaining steps were the same as in Example 1.
[0063] Preparation of CDs@LDHs molecular imprinting polymer: The first blending time was 90 min, and the second blending was divided into two steps. The first step was to add CDs and stir for 30 min. The second step was to add 1.5 mL of tetraethyl silicate, 250 µL of ammonia water and ultrapure water and stir for 5 h. The mass ratio of methanol to acetic acid was 10:1. The remaining steps were the same as in Example 1.
[0064] Comparative Example 1
[0065] The steps for preparing CDs@LDHs non-molecular imprinting polymers were the same as those in Example 1, except that the template molecule myclobutanil was not added.
[0066] Comparative Example 2
[0067] The molecular imprinted polymer was prepared in the same steps as in Example 1, except that no functional monomer was added.
[0068] Comparative Example 3
[0069] The molecular imprinted polymer was prepared in the same manner as in Example 1, except that CDs were not added.
[0070] Comparative Example 4
[0071] The molecular imprinted polymer was prepared in the same steps as in Example 1, except that LDHs were not added.
[0072] The following is a test on the specific reaction of myclobutanil on the polymers obtained in Examples 1-3 and Comparative Examples 1-4 to determine the optimal reaction conditions:
[0073] Comparative test example 1
[0074] Test the optimal reaction time of fluorescence quenching reaction:
[0075] Take 2 mg of the CDs@LDHs molecular imprinting polymer in Example 1 and disperse it evenly in 8 mL of anhydrous ethanol to obtain a test solution; add 1 ml of buffer (pH=8), 4 ml of the test solution and 2 ml of myclobutanil ethanol solution (0.008 µg / mL) in a 10 mL colorimetric tube, shake well and measure the fluorescence intensity every 5-10 minutes until 100 minutes. Replace the CDs@LDHs molecular imprinting polymer with the CDs@LDHs non-molecular imprinting polymer obtained in Comparative Example 1, and repeat the above steps.
[0076] like Figure 8 (abscissa: reaction time / min, ordinate: fluorescence quenching rate / 1-F / F0; from top to bottom are the measurement curves of CDs@LDHs molecular imprinting polymer and CDs@LDHs non-molecular imprinting polymer) As shown, when the reaction time is <55min, the fluorescence quenching rate shows an upward trend as the reaction proceeds, that is, when <55min, the fluorescence quencher (myclobutanil) is not fully reacted. When the reaction time is ≥55min, CDs@LDHs molecular imprinting polymer or CDs@LDHs non-molecular imprinting polymer reacts most fully with myclobutanil; in addition, the fluorescence intensity change trend of CDs@LDHs non-molecular imprinting polymer (Comparative Example 1) is relatively gentle in different myclobutanil concentrations, that is, the sensitivity is poorer than that of CDs@LDHs molecular imprinting polymer in Example 1; similarly, the sensitivity of the polymers in Comparative Examples 2-4 is poorer than that in Example 1.
[0077] The optimal reaction time of the fluorescence quenching reaction of the CDs@LDHs molecular imprinted polymer obtained in Example 2-3 was further measured. It was found that when the reaction time was 55 min, the fluorescence quenching reaction was most sufficient. Therefore, 55 min was selected as the reaction time for subsequent tests.
[0078] Comparative test example 2
[0079] Test the optimal pH for fluorescence quenching reaction:
[0080] Take 2 mg of the CDs@LDHs molecular imprinting polymer in Example 1 and disperse it evenly in 8 mL of anhydrous ethanol to obtain a test solution (if it is insufficient, it can be re-prepared), add 1 ml of buffer solution (the pH of the buffer solution in the eight colorimetric tubes is 2, 4, 6, 7, 8, 9, 10, 12, respectively), 4 ml of the test solution and 2 ml of myclobutanil ethanol solution (0.008 µg / mL) to eight 10 mL colorimetric tubes, shake well for 55 minutes, and measure the fluorescence intensity of the substance in the colorimetric tube. Replace the CDs@LDHs molecular imprinting polymer with the CDs@LDHs non-molecular imprinting polymer obtained in Comparative Example 1, and repeat the above steps.
[0081] like Fig. 9 (abscissa: acidity / pH, ordinate: fluorescence quenching rate / 1-F / F0; from top to bottom are the measurement curves of CDs@LDHs molecular imprinting polymer and CDs@LDHs non-molecular imprinting polymer), at pH=8, the fluorescence quenching rate of CDs@LDHs molecular imprinting polymer is the largest, that is, the fluorescence intensity changes greatly before and after quenching, and it is easier to measure accurately; in addition, in the pH range of 2-12, the fluorescence quenching rate of CDs@LDHs molecular imprinting polymer is greater than that of CDs@LDHs non-molecular imprinting polymer (Comparative Example 1); similarly, it is also greater than the polymers obtained in Comparative Examples 2-4.
[0082] The optimal pH of the CDs@LDHs molecular imprinted polymer obtained in Example 2-3 was further measured. It was found that the fluorescence quenching rate was the largest at pH=8. Therefore, pH=8 was selected as the pH value of the buffer solution in subsequent tests.
[0083] Comparative test example 3
[0084] Test the optimal dosage of CDs@LDHs molecular imprinting polymer:
[0085] Different weights of CDs@LDHs molecular imprinting polymers (0.5 mg, 1 mg, 2 mg) of Example 1 and Comparative Example 1 were dispersed evenly in 8 mL of anhydrous ethanol to obtain test solutions of different concentrations; multiple 10 mL colorimetric tubes were divided into 3 groups, and 1 ml of buffer solution (pH = 8), 4 ml of test solutions of different concentrations (0.0625 mg / L test solution was added to the first group; 0.125 mg / L test solution was added to the second group; 0.25 mg / L test solution was added to the third group) and 2 ml of myclobutanil ethanol solution (the concentrations of the three groups were all within the range of 0.001-0.012 µg / mL), and after shaking for 55 minutes, the fluorescence intensity was measured in turn. The CDs@LDHs molecular imprinting polymer was replaced with the CDs@LDHs non-molecular imprinting polymer obtained in Comparative Example 1, and the above steps were repeated.
[0086] like Fig.10 (Abstract: myclobutanil concentration / µg / mL, vertical axis: fluorescence quenching rate / 1-F / F0, starting from 0.012µg / mL, from top to bottom: CDs@LDHs molecular imprinting polymer dosage of 2mg, CDs@LDHs molecular imprinting polymer dosage of 1mg, CDs@LDHs non-molecular imprinting polymer dosage of 1mg, CDs@LDHs non-molecular imprinting polymer dosage of 2mg, CDs@LDHs molecular ... As shown in the regression curves of the CDs@LDHs molecular imprinting polymer with a dosage of 0.5 mg and the CDs@LDHs non-molecular imprinting polymer with a dosage of 0.5 mg), when the dosage of CDs@LDHs molecular imprinting polymer is 2 mg, the fluorescence response of CDs@LDHs molecular imprinting polymer is the most sensitive (y=84.737x-0.0166, the slope 84.737 is the largest, that is, for different concentrations of myclobutanil, the fluorescence intensity changes more significantly), and the linear relationship is also relatively good (that is, R 2 =0.9903), and the regression curves of comparative examples 2-4 were measured in the same way. It can be seen that when the dosage of CDs@LDHs molecular imprinting polymer is 2 mg, the fluorescence response of CDs@LDHs molecular imprinting polymer is most sensitive.
[0087] Similarly, the optimal dosage of the CDs@LDHs molecular imprinting polymer obtained in Examples 2-3 was continued to be measured. It was found that when the dosage was 2 mg, the fluorescence quenching rate of the CDs@LDHs molecular imprinting polymer was the largest and the fluorescence response was the most sensitive. Therefore, 2 mg was selected as the dosage of the CDs@LDHs molecular imprinting polymer in subsequent tests.
[0088] Comparative test example 4
[0089] Test the treatment effect of CDs@LDHs molecular imprinting polymer on different concentrations of myclobutanil:
[0090] Add thiamethoxam to anhydrous ethanol to prepare thiamethoxam solutions of different concentrations (0-0.015µg / mL); take 2mg of the CDs@LDHs molecular imprinting polymer in Example 1 and dissolve it in 8mL of anhydrous ethanol to prepare a test solution; take 4mL of the test solution, 2mL of thiamethoxam solutions of different concentrations, and 1mL of buffer (pH=8) and add them to multiple 10mL centrifuge tubes respectively, mix them, shake on a shaker for 55min, and measure the fluorescence spectra of the CDs@LDHs molecular imprinting polymer at different thiamethoxam concentrations. Replace the CDs@LDHs molecular imprinting polymer with the CDs@LDHs non-molecular imprinting polymer obtained in Comparative Example 1, repeat the above steps, and measure the fluorescence spectra of the CDs@LDHs non-molecular imprinting polymer at different thiamethoxam concentrations.
[0091] like Fig.11 (abscissa: myclobutanil concentration / µg / mL, ordinate: fluorescence quenching rate / 1-F / F0; from top to bottom are the measurement curves of CDs@LDHs molecular imprinted polymer and CDs@LDHs non-molecular imprinted polymer), when the myclobutanil concentration is greater than 0.012µg / mL, the fluorescence quenching rate hardly changes, that is, when greater than 0.012µg / mL, the adsorption of CDs@LDHs molecular imprinted polymer tends to saturation, at which time the fluorescence quenching rate and myclobutanil concentration no longer correspond one to one, so the appropriate myclobutanil measurement range is 0-0.012µg / mL; at the same time, the fluorescence quenching rate of CDs@LDHs molecular imprinted polymer for different concentrations (0-0.012µg / mL) of myclobutanil changes more significantly, that is, the response effect is better, the sensitivity during detection is higher, and the error is smaller; similarly, compared with Comparative Examples 2-4, the response effect of CDs@LDHs molecular imprinted polymer in Example 1 is also better.
[0092] Similarly, the treatment effect of the CDs@LDHs molecular imprinted polymer obtained in Example 2-3 on different concentrations of myclobutanil was measured. It can be seen that when the myclobutanil concentration was <0.012 µg / mL, as the myclobutanil concentration increased, the fluorescence quenching rate of the CDs@LDHs molecular imprinted polymer increased regularly, which means that at this time, the specific sites in the CDs@LDHs molecular imprinted polymer were not completely occupied by myclobutanil. At this time, the content of myclobutanil can be inferred based on the fluorescence quenching rate. Therefore, the suitable myclobutanil detection concentration of the CDs@LDHs molecular imprinted polymer of the present invention is 0-0.012 µg / mL.
[0093] Example 4
[0094] Draw a standard curve:
[0095] Take 2 mg of the CDs@LDHs molecular imprinting polymer in Example 1 and disperse it evenly in 8 mL of anhydrous ethanol to obtain a test solution. Add 1 mL of buffer solution (pH=8), 4 mL of test solution and 2 mL of myclobutanil ethanol solution with a concentration in the range of 0.000-0.012 µg / mL (preferably, 0, 0.0005, 0.0012, 0.0018, 0.0032, 0.0045, 0.0059, 0.0078, 0.0096, and 0.012, the linear relationship is best) to a 10 mL colorimetric tube. Oscillate for 55 minutes, and measure the fluorescence intensity change of the CDs@LDHs molecular imprinting polymer under different concentrations of myclobutanil in the emission mode of the fluorescence spectrophotometer, so as to draw a curve of the relationship between the fluorescence quenching intensity and the myclobutanil concentration, as shown in FIG. Fig.12 (abscissa: myclobutanil concentration / µg / mL, ordinate: fluorescence quenching rate / 1-F / F0). The linear relationship of the standard curve of the CDs@LDHs molecular imprinting polymer-myclobutanil system was determined to be y=97.999X-0.0225, and the correlation coefficient (R 2 ) is 0.9963, and the linear relationship is good.
[0096] Measuring the content of myclobutanil in wheat:
[0097] Take 5.5g of wheat that has not been treated with myclobutanil, grind it in a mortar and divide it into three portions. Add known standard amounts of myclobutanil to each portion, which are 0.04351µg / g, 0.09108µg / g and 0.2300µg / g (µg / g: the mass of myclobutanil added per gram of wheat) to simulate the process of wheat absorbing residual myclobutanil. Place them in three 250mL conical flasks, add 20.0mL of ethanol to each conical flask, shake well, place in the refrigerator for 12h, ultrasonicate for 1.0h and then centrifuge (centrifugal speed is 4000rmin) -1 , centrifugation time is 0.5h), collect the supernatant, and continue to add 20.0mL of ethanol to the solid obtained by centrifugation, repeat the above step of collecting the supernatant twice, mix the supernatants obtained three times for use, and label them M1, M2 and M3 respectively.
[0098] Using the CDs@LDHs molecular imprinting polymer prepared in Example 1, according to the above experimental steps, the fluorescence quenching rates of the three labels were measured respectively using a fluorescence spectrophotometer, and the theoretical amount of myclobutanil was determined based on the drawn standard curve, and then the spiked measured amount (µg / g) and recovery rate (%) were calculated. The detailed data are shown in Table 1.
[0099]
[0100] The experimental results showed that the recovery rate of myclobutanil in wheat was 93.6-99.7%, with good measurement accuracy; the RSD was 3.2, and the measurement results had good reproducibility.
[0101] Comparative Example 5
[0102] The preparation steps of wheat supernatant were the same as those in Example 4, except that the myclobutanil content was measured using gas chromatography.
[0103] Comparative Example 6
[0104] The preparation steps of wheat supernatant are the same as those in Example 4, except that ultrasonic extraction is used in combination with gas chromatography to measure the content of myclobutanil. The measurement results are shown in Table 2.
[0105]
[0106] The experimental results show that CDs@LDHs molecular imprinting polymer has the advantages of wide linear range, high sensitivity, and can effectively detect trace levels of myclobutanil in crops (such as wheat); it has the advantages of specificity for the detection of myclobutanil, high accuracy of the detection results (recovery rate range is less than and close to 100%), small error, and good reproducibility of the measurement results (RSD=3.2). In addition, compared with the other two detection methods, the CDs@LDHs molecular imprinting polymer in the present invention can be prepared in advance and stored for a long time, and has the advantages of small dosage, convenient operation, low cost and repeated recycling during measurement, and has good application potential.
[0107] Although the present invention is described in detail by way of the accompanying drawings and in combination with the embodiments, the present invention is not limited thereto. Without departing from the spirit and essence of the present invention, a person of ordinary skill in the art may make various equivalent modifications or substitutions to the embodiments of the present invention, and these modifications or substitutions shall all be within the scope of the present invention.
Claims
1. A method for preparing a CDs@LDHs molecularly imprinted polymer, characterized in that: LDHs was reacted with template molecules and functional monomers once, and then CDs, tetraethyl silicate and ammonia solution were added in sequence for secondary reaction and elution, and finally CDs@LDHs molecular imprinting polymer was obtained; CDs were prepared by hydrothermal reaction of citric acid, ethanol and silane coupling agent; LDHs is Mg / Fe-LDHs, and Mg / Fe-LDHs is prepared by co-precipitation by introducing sodium hydroxide solution into magnesium chloride hexahydrate and ferric chloride hexahydrate; the concentration of the sodium hydroxide solution is 9.0-10.5 mol / L; the ratio of the added amounts of magnesium chloride hexahydrate, ferric chloride hexahydrate and sodium hydroxide solution is (0.65-0.75):(0.15-0.25):1, wherein the units of magnesium chloride hexahydrate and ferric chloride hexahydrate are g, and the unit of sodium hydroxide solution is mL.
2. The method for preparing the CDs@LDHs molecularly imprinted polymer according to claim 1, characterized in that: The silane coupling agent is KH792; the ratio of the added amounts of citric acid, ethanol and silane coupling agent is (0.045-0.055): 1:1, wherein the unit of citric acid is g, and the unit of ethanol and silane coupling agent is mL; the hydrothermal reaction temperature is 175-190°C, and the hydrothermal reaction time is 4.5-7h.
3. The method for preparing the CDs@LDHs molecularly imprinted polymer according to claim 1, characterized in that: The coprecipitation temperature is 20-40°C, and the coprecipitation time is 12-20 min.
4. The method for preparing the CDs@LDHs molecularly imprinted polymer according to claim 1, characterized in that: The ratio of the added amounts of LDHs, functional monomer, tetraethyl silicate and ammonia water is 1:14:60:(7-10), wherein the unit of LDHs is mg, and the unit of functional monomer, tetraethyl silicate and ammonia water is µL; the molar ratio of the template molecule and the functional monomer is 1:3; the template molecule is myclobutanil, and the functional monomer is 3-aminopropyltriethoxysilane; the ratio of the added amounts of LDHs and CDs is 25:0.1, wherein the unit of LDHs is mg, and the unit of CDs is mL.
5. The method for preparing the CDs@LDHs molecularly imprinted polymer according to claim 1, characterized in that: The primary reaction time is 60-120 minutes; the secondary reaction time is 5-6.5 hours; a mixture of methanol and acetic acid is used for elution, and the mass ratio of methanol to acetic acid is (8-10):
1.
6. An application of a CDs@LDHs molecularly imprinted polymer prepared by the preparation method according to any one of claims 1 to 5, characterized in that: The CDs@LDHs molecular imprinting polymer is prepared into a test solution, and the test solution and buffer solution are respectively subjected to fluorescence quenching with different concentrations of myclobutanil standard solutions, and the corresponding relationship between the fluorescence quenching rate of the test solution and the myclobutanil concentration is measured to obtain a standard curve; the test solution and buffer solution are re-prepared, and crops containing myclobutanil are made into crop grinding liquid, and the test solution and buffer solution are subjected to fluorescence quenching with the crop grinding liquid, and the fluorescence quenching rate of the re-prepared test solution is detected, and the myclobutanil concentration in the crop grinding liquid is obtained according to the corresponding relationship on the standard curve.
7. The use of the CDs@LDHs molecularly imprinted polymer according to claim 6, characterized in that: The test solution was prepared by dispersing CDs@LDHs molecular imprinting polymer in ethanol, and the concentration of CDs@LDHs molecular imprinting polymer was 0.25 mg / mL; the buffer solution was a mixture of disodium hydrogen phosphate and sodium dihydrogen phosphate, and the pH value of the buffer solution was 8; the volume ratio of the test solution, buffer solution, myclobutanil standard solution and crop grinding solution was 4:1:2:
2.
8. The use of the CDs@LDHs molecularly imprinted polymer according to claim 6, characterized in that: The fluorescence quenching rate was measured by fluorescence spectrophotometer; the fluorescence quenching temperature was 20-35°C, and the fluorescence quenching time was 55 min.
9. The use of the CDs@LDHs molecularly imprinted polymer according to claim 6, characterized in that: The concentration of the myclobutanil standard solution is 0-0.012µg / mL; the detection range of the myclobutanil concentration in the crop grinding liquid is 0-0.3053µg / g, where g represents the crop mass.
10. The use of the CDs@LDHs molecularly imprinted polymer according to claim 9, characterized in that: The concentration values of the myclobutanil standard solution were 0µg / mL, 0.0005µg / mL, 0.0012µg / mL, 0.0018µg / mL, 0.0032µg / mL, 0.0045µg / mL, 0.0059µg / mL, 0.0078µg / mL, 0.0096µg / mL and 0.012µg / mL, respectively.
Citation Information
Patent Citations
Preparation method and application of myclobutanil molecularly imprinted inverse opal photonic crystal hydrogel sensor
CN111635552A
Preparation method of self-supporting molecularly imprinted polymer film
CN102432778A